Differences in lung function between children with sickle cell anaemia from West Africa and Europe. Issue 12 (17th October 2019) - Arigliani, Michele; Castriotta, Luigi; Zubair, Ramatu; Dogara, Livingstone Gayus; Zuiani, Chiara; Raywood, Emma; Vecchiato, Katy; Petoello, Enrico; Sunday, Ashel Dache; Ndoro, Sharon; Canciani, Mario Canciano; Gupta, Atul; et al.
Abstract : Introduction: Lung function abnormalities are common in sickle cell anaemia (SCA) but data from sub-Saharan Africa are limited. We hypothesised that children with SCA from West Africa had worse lung function than their counterparts from Europe. Methods: This prospective cross-sectional study evaluated spirometry and anthropometry in black African individuals with SCA (haemoglobin phenotype SS) aged 6–18 years from Nigeria and the UK, when clinically stable. Age-matched controls were also included in Nigeria to validate the Global Lung Initiative spirometry reference values. Results: Nigerian SCA patients (n=154) had significant reductions in both FEV1 and FVC of 1 z-score compared with local controls (n=364) and 0.5 z-scores compared with the UK patients (n=101). Wasting (body mass index z-score<−2) had a prevalence of 27% in Nigerian patients and 7% in the UK ones (p<0.001). Among children with SCA, being resident in Nigeria (OR 2.4, 95% CI 1.1 to 4.9), wasting (OR 2.3, 95% CI 1.1 to 5.0) and each additional year of age (OR 1.2, 95% CI 1.1 to 1.4) were independently associated with increased risk of restrictive spirometry (FVC z-score<−1.64+FEV1 /FVC≥−1.64). Conclusions: This study showed that chronic respiratory impairment is more severe in children with SCA from West Africa than Europe. Our findings suggest the utility of implementing respiratory assessment in African children with SCA to early identify those with chronic lung injury, eligible for closer follow-up and more aggressive therapies.